Measurements of underwater operational noise caused by offshore wind turbine off the southwest coast of Korea - Yoon, Young Geul; Han, Dong-Gyun; Choi, Jee Woong (Frontiers in Marine Science, 2023)
As interest in the development of renewable energy increases, a large number of offshore wind farms are being built worldwide. Accordingly, the potential impacts of underwater operational noise on marine ecosystems have become an issue, and thus it is necessary to understand the mechanisms and acoustic characteristics of underwater operational noise for the environmental impact assessment. For this paper, underwater noise was measured for about 10 days near a 3-MW wind turbine off the southwest coast of Korea, and the acoustic characteristics of the operational noise and its relationship with rotor speed were investigated. The tonal frequencies of the underwater operational noise varied with rotor speed, and particularly the peak level at a frequency of 198 Hz increased by 20 dB or more at the rated rotor speed. Additional experiments were conducted to determine the relationship between underwater noise and wind turbine tower vibration, and finally, the underwater noise correlated highly with the tower vibration acceleration signal, wind speed, and rotor speed, with correlation coefficients of 0.95 or higher.